Social-ecological resilience of coastal tourism to climate change: A case study of Depok Beach, Bantul, Indonesia - I Putu Hardani Hesti Duari; Robertus Saptoto; Waode Asti Ananta; Pedro Triadi Cahyo; Mutiara Maulidina; Naumi Berliana; Apriasnita Apriasnita (Journal of Rural Tourism, 2026)
Purpose – This study aims to analyze how climate change impacts the sustainability of coastal tourism destinations, focusing on Depok Beach, Bantul. It explores the socio-ecological resilience of coastal communities and examines the adaptation and mitigation strategies developed to address environmental threats such as abrasion and extreme weather. Methodology/Design/Approach – Through documentation studies, in-depth interviews, and field observations, the research methodology employed descriptive qualitative approaches.  Fishermen, traders, and managers of tourism awareness groups (Pokdarwis) were among the key informants. Findings – The findings indicate that cross-sectoral cooperation with the government and educational institutions, local organization strengthening, and economic resource diversification all contribute to the development of socio-ecological resilience.  Reforestation programs, disposal of waste, and the implementation of eco-friendly tourism practices are all a component of mitigation efforts.  Conversely, adaptation happens through modifications to corporate policies, innovations in digital marketing. Conversely, adaptation is achieved through modifications to corporate procedures, advancements in digital marketing, and readiness for abrasion effects.  These results highlight how crucial it is to combine social, economic, and ecological factors in order to increase coastal communities' and tourism's resilience to climate changeOriginality/value – This study uniquely integrates socio-ecological resilience with practical adaptation and mitigation strategies in coastal tourism sustainability. Focusing on Depok Beach, Bantul, it highlights local collaboration among communities, government, and academia, while introducing digital marketing innovation as an adaptive response to climate challenges. The research contributes an integrative model linking ecological sustainability with socio-economic resilience in coastal destinations.